Glycine-based treatment ameliorates NAFLD by modulating fatty acid oxidation, glutathione synthesis, and the gut microbiome - Rom, Oren; Liu, Yuhao; Liu, Zhipeng; Zhao, Ying; Wu, Jianfeng; Ghrayeb, Alia; Villacorta, Luis; Fan, Yanbo; Chang, Lin; Wang, Lu; Liu, Cai; Yang, Dongshan; et al. (Science translational medicine, 2020)
Nonalcoholic fatty liver disease (NAFLD) including nonalcoholic steatohepatitis (NASH) has reached epidemic proportions with no pharmacological therapy approved. Lower circulating glycine is consistently reported in patients with NAFLD, but the causes for reduced glycine, its role as a causative factor, and its therapeutic potential remain unclear. We performed transcriptomics in livers from humans and mice with NAFLD and found suppression of glycine biosynthetic genes, primarily alanine-glyoxylate aminotransferase 1 ( ). Genetic ( mice) and dietary approaches to limit glycine availability resulted in exacerbated diet-induced hyperlipidemia and steatohepatitis, with suppressed mitochondrial/peroxisomal fatty acid β-oxidation (FAO) and enhanced inflammation as the underlying pathways. We explored glycine-based compounds with dual lipid/glucose-lowering properties as potential therapies for NAFLD and identified a tripeptide (Gly-Gly-L-Leu, DT-109) that improved body composition and lowered circulating glucose, lipids, transaminases, proinflammatory cytokines, and steatohepatitis in mice with established NASH induced by a high-fat, cholesterol, and fructose diet. We applied metagenomics, transcriptomics, and metabolomics to explore the underlying mechanisms. The bacterial genus sensu stricto was markedly increased in mice with NASH and decreased after DT-109 treatment. DT-109 induced hepatic FAO pathways, lowered lipotoxicity, and stimulated de novo glutathione synthesis. In turn, inflammatory infiltration and hepatic fibrosis were attenuated via suppression of NF-κB target genes and TGFβ/SMAD signaling. Unlike its effects on the gut microbiome, DT-109 stimulated FAO and glutathione synthesis independent of NASH. In conclusion, impaired glycine metabolism may play a causative role in NAFLD. Glycine-based treatment attenuates experimental NAFLD by stimulating hepatic FAO and glutathione synthesis, thus warranting clinical evaluation.